Natural Products Targeting Autophagy via the PI3K/Akt/mTOR Pathway as Anticancer Agents - Sun, Hui; Wang, Zhaoye; Sebastian Yakisich, Juan (Anti-Cancer Agents in Medicinal Chemistry, 2013)
The phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway is a key regulator of authophagy. Natural products show anticancer activity and often induce apoptosis or autophagy. The crosstalk between these two types of cell death makes autophagy an interesting target since drugs targeting this process not only can induce cell death by inducing autophagy but can also sensitize cells to apoptosis. Autophagy is also a protective mechanism associated with increased resistance to chemotherapy. In this review, we discuss natural products known to induce autophagy cell death in cancer cells via the PI3K/Akt/mTOR pathway.
Keywords: cancer stem cell